Development of Bahiagrass Fertilization Recommendations: 1990-2005 - Edward A. Hanlon; Rao Mylavarapu; Ikechukwu V. Ezenwa (EDIS)
This document provides a history of past Bahiagrass recommendation decision-making, and should aid the Forage Fertilization Working Group with future recommendation development. Ranchers, forage producers, and other interested parties may also use the information in this document to understand the basis for UF/IFAS Bahiagrass liming and fertilization recommendations. This document is SL-237, one of a series of the Soil and Water Science Department, UF/IFAS Extension. Original publication date January 2006. Revised March 2006.